PERFORMANCE OF HELICAL PILES UNDER DIFFERENT INSTALLATION AND LOADING CONDITIONS: AN EXPERIMENTAL AND ANALYTICAL REVIEW (International Seven Journal of Multidisciplinary, 2024)
The performance of helical piles under varying installation and loading conditions has been widely investigated through experimental studies and numerical modeling. Installation time has proven to be a determining factor in axial resistance due to the “setup” phenomenon, which is especially relevant in cohesive soils. The recovery of soil strength after disturbance can increase load-bearing capacity over time, whereas rapid installations tend to induce greater disturbance and lower initial strength. Research such as that by Wang et al. (2025) proposes innovative over-flighted installation techniques to reduce insertion effort and improve in-service resistance. The helix geometry and spacing, as shown by Lanyi-Bennett and Deng (2019), directly affect the resistance mechanisms mobilized, with adequate spacing favoring individual bearing behavior. Schiavon et al. (2024) showed that reused piles, when reinstalled deeper, can partially or fully recover their capacity under cyclic loading. The influence of helix deformation, studied by Malik et al. (2019), reveals that the performance of piles with bent helices can be significantly reduced, emphasizing the need for optimized design. Furthermore, Malik and Kuwano (2020) highlight performance loss under one-way cyclic loading, stressing the importance of accounting for these effects in structures subjected to repetitive loads. The study by Masatoshi et al. (2017) confirms the reduction in capacity under cyclic reversal loading but also shows that continuous helix piles maintain their tip resistance, making them effective in environments with cyclic demands. Collectively, the studies reinforce the superiority of helical piles over traditional alternatives, emphasizing the importance of design tailored to real soil and loading conditions.